Using action learning sets to support change in end-of-life care. Issue 2 (2nd May 2017) - Gillett, Karen; Reed, Liz; Bryan, Liz
Abstract : Purpose: The purpose of this paper is to describe the delivery of facilitated action learning sets as an integral component of a multidisciplinary end-of-life care course. Design/methodology/approach: The educational intervention described in this paper is delivered by specialist palliative care practitioners to those working with dying patients and their families in non-specialist settings. The programme consists of two components: the first taught/experience-based component takes place in a hospice. The second integral component involves action learning sets which are facilitated by specialist palliative care staff over a six-month period. This paper reports the challenges, learning and benefits of using action learning sets to improve end-of-life care. Findings: Action learning sets provide support which enables staff to implement changes to end-of-life care. Participants in the successful action learning sets were motivated to change practice and identified themselves as change agents. Management support was vital to allow participants the authority to implement changes to practice. Practical implications: Facilitators need to gain participant and management commitment to the action learning process before the programme begins if they are to be successful in achieving changes to end-of-life care. Originality/value: Hospices and other health care organisations work in partnership to deliver this programme, and this paper demonstrates how action learning sets can increase mutual understanding and communication between specialist and non-specialist end-of-life care settings.